Synthesis of Mo2C and W2C Nanoparticle Electrocatalysts for the Efficient Hydrogen Evolution Reaction in Alkali and Acid Electrolytes - Hussain, Sajjad; Vikraman, Dhanasekaran; Feroze, Asad; Song, Wooseok; An, Ki-Seok; Kim, Hyun-Seok; Chun, Seung-Hyun; Jung, Jongwan (Frontiers in Chemistry, 2019)
The synthesis of low cost, high efficacy, and durable hydrogen evolution electrocatalysts from the non-noble metal group is a major challenge. Herein, we establish a simple and inexpensive chemical reduction method for producing molybdenum carbide (Mo2C) and tungsten carbide (W2C) nanoparticles that are efficient electrocatalysts in alkali and acid electrolytes for hydrogen evolution reactions (HER). Mo2C exhibits outstanding electrocatalytic behavior with an overpotential of −134 mV in acid medium and of −116 mV in alkaline medium, while W2C nanoparticles require an overpotential of −173 mV in acidic medium and −130 mV in alkaline medium to attain a current density of 10 mA cm−2. The observed results prove the capability of high- and low-pH active electrocatalysts of Mo2C and W2C nanoparticles to be efficient systems for hydrogen production through HER water electrolysis.